2013
DOI: 10.1371/journal.pone.0074444
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of pstS and phoB on Quorum Sensing and Swarming Motility in Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa is an opportunistic pathogen that can cause a wide range of infections and inflammations in a variety of hosts, such as chronic biofilm associated lung infections in Cystic Fibrosis patients. Phosphate, an essential nutrient, has been recognized as an important signal that affects virulence in P. aeruginosa. In the current study we examined the connection between phosphate regulation and surface motility in P. aeruginosa. We focused on two important genes, pstS, which is involved in phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 38 publications
1
54
0
Order By: Relevance
“…These swarming‐associated genes, including flagella genes ( flgBCDEFGHIJKL ) and rhamnolipid biosynthesis genes ( rhIRBA ), showed no sign of repression in H300. It has been reported that phosphorylated PhoB is able to increase swarming mobility by up‐regulating the Rhl quorum sensing system, which resulted in hyper production of rhamonlipids (Blus‐Kadosh et al ., ). On the contrary, in our study the swarming mobility (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…These swarming‐associated genes, including flagella genes ( flgBCDEFGHIJKL ) and rhamnolipid biosynthesis genes ( rhIRBA ), showed no sign of repression in H300. It has been reported that phosphorylated PhoB is able to increase swarming mobility by up‐regulating the Rhl quorum sensing system, which resulted in hyper production of rhamonlipids (Blus‐Kadosh et al ., ). On the contrary, in our study the swarming mobility (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…One Node164pos gene encodes PhoB, a transcription factor in the PhoR-PhoB two-component system that responds to low environmental phosphate in P. aeruginosa (Bielecki et al, 2015; Blus-Kadosh et al, 2013; Santos-Beneit, 2015). Further, Node164pos is the signature most enriched for a previously defined PhoB regulon (FDR q-value of 8.1e-29 in hypergeometric test).…”
Section: Resultsmentioning
confidence: 99%
“…In P. aeruginosa, Pi limitation promoted bacterial hyper-swarming through PhoB upregulation of rhlR expression resulting in increased rhamnolipid production. 51 The rhamnolipid biosurfactants facilitate swarming motility. This may explain the hyper-motile phenotype exhibited by the Δpst mutant and the motility defect observed in the ΔphoB mutant.…”
Section: Roles Of Phob and Pi Response In Variousmentioning
confidence: 99%